Sprayable hydrogel for biomedical applications. (21st April 2022) - Liao, Yingying; Xie, Luoyijun; Ye, Jiahui; Chen, Tong; Huang, Tong; Shi, Leilei; Yuan, Miaomiao
Abstract : Schematic illustration of sprayable hydrogels for biomedical application. Abstract : Polymeric hydrogels have extraordinary potential to be utilized for biomedical applications. Recently, sprayable hydrogels have received increasing attention for their biocompatibility, degradability, tunable mechanical properties and rapid spray-filming abilities. In this review, hydrogel-based biomaterials, especially those based on natural polymers, such as polysaccharides and proteins, have been explained. The focus of this review lies on illuminating recent advances in sprayable hydrogel systems and highlighting the properties and applications of sprayable hydrogels, such as wound management, postoperative adhesion and cancer therapeutics. In addition, future research directions and challenges are also discussed.